Nonionic surfactants and dispersants for biopolishing and stonewashing with Hypocrea jecorina cellulases. (14th December 2012) - Zilz, Luana; Rau, Martinho; Budag, Nelson; Scharf, Mauro; Cavaco‐Paulo, Artur; Andreaus, Jürgen
<x xml:space="preserve">Abstract</x> Cellulases are widely applied in textile finishing, such as for the removal of protruding surface fibrils to reduce pilling propensity and to achieve the worn‐out look in denim garments. The main drawback of enzymatic denim processing is the back‐staining of indigo, which reduces the desired blue–white contrast. Alongside an accurate selection of the type of cellulase or vigorous post‐washing of the garments, the simultaneous application of auxiliaries in the enzymatic treatment may help to reduce back‐staining and improve cellulase efficiency. In the present work, the influence of additives such as surfactants and dispersing agents on indigo adsorption and on the treatment of an undyed cotton fabric with Hypocrea jecorina cellulases was investigated. Indigo adsorption was successfully reduced by more than 75% with ethoxylated nonionic surfactants at concentrations below 0.2 g l−1. The weight loss of cotton fabrics after 120 min treatment was significantly increased with nonionic surfactants and polyvinylpyrrolidone. It could be further shown that protein adsorption on the cotton fabric decreased with the increasing concentration of the additives, while the nonionic surfactants were more efficient than the polyvinylpyrrolidone. Adsorption of a complete cellulase mixture was affected differently by the surfactants than by an exoglucanase‐free endoglucanase‐rich preparation.